1988
DOI: 10.1111/j.1365-2788.1988.tb01442.x
|View full text |Cite
|
Sign up to set email alerts
|

A low‐cost method for simultaneous video‐recording of ambulant subject and electroencephalograph: the Quarrier's system*

Abstract: ABSTRACT. A system is described by means of which the ambulant subject may be video‐filmed over several hours with the electroencephalograph superimposed on the same tape, allowing correlations to be observed in the active state. Our first subjects have been girts with Rett syndrome. Requirements are: one portable video camera/recorder, a conventional e.e.g. machine, the ‘Medilog 9000’ system for prolonged ambulatory recording (Oxford Medical), a specialized video mixer (videogram For AFVG600, commercially av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…3,4 In another study, simple improvisation was used to combine a conventional ambulatory EEG system with a portable video camera set up in the patient's home, with offline combining of the EEG and video for simultaneous viewing. 5 A case study reported the benefit of home recording for monitoring the patient's treatment. 6 Probably the best-established system combines EEG and video into a single portable unit taken by the patient to their home, after EEG connection in the clinic 7 ; however, this system differs from our described here in that it is ''unattended'' -that is, there is no professional staff involvement in the patient's home, whereas we describe here an ''attended'' system, with professionals visiting the patient's home during monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In another study, simple improvisation was used to combine a conventional ambulatory EEG system with a portable video camera set up in the patient's home, with offline combining of the EEG and video for simultaneous viewing. 5 A case study reported the benefit of home recording for monitoring the patient's treatment. 6 Probably the best-established system combines EEG and video into a single portable unit taken by the patient to their home, after EEG connection in the clinic 7 ; however, this system differs from our described here in that it is ''unattended'' -that is, there is no professional staff involvement in the patient's home, whereas we describe here an ''attended'' system, with professionals visiting the patient's home during monitoring.…”
Section: Introductionmentioning
confidence: 99%